1997
DOI: 10.1289/ehp.97105644
|View full text |Cite
|
Sign up to set email alerts
|

Methylsulfonyl metabolites of PCBs and DDE in human tissues.

Abstract: Methylsulfonyl metabolites of chlorinated biphenyls (MeSO2-CBs) and p,p'-DDE (MeSO2-DDEs) were determined in human adipose and liver tissues obtained at autopsy of seven Swedish individuals 47-80 years of age. Twenty MeSO2-CBs and two MeSO2-DDEs were found in the analyzed samples. In adipose tissue, most of the 4-MeSO2-CBs were found at higher concentrations than the corresponding 3-MeSO2-CBs and, in all samples of adipose tissue, 4-MeSO2-2,2',3',4',5-pentaCB (4-87) and 4-MeSO2-2,2',3,4',5',6-hexaCB (4-149) oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…The metabolic behavior of some of PCBs with 3,4-substitution is similar to the metabolism of PCBs with 2,5-substitution (44). To date, a number of MeSO 2 metabolites have been identified in marine mammals (45)(46)(47) as well as in human milk (48) and tissues (49). Most of them are those arising from pentaCB and hexaCB with a 2,5-dichloro or a 2,3,6-trichloro substitution.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic behavior of some of PCBs with 3,4-substitution is similar to the metabolism of PCBs with 2,5-substitution (44). To date, a number of MeSO 2 metabolites have been identified in marine mammals (45)(46)(47) as well as in human milk (48) and tissues (49). Most of them are those arising from pentaCB and hexaCB with a 2,5-dichloro or a 2,3,6-trichloro substitution.…”
Section: Discussionmentioning
confidence: 99%
“…They accumulate with high selectivity in certain tissues, such as liver and lung (Letcher et al, 2000, Bergman et al, 1979, Larsson and Bergman, 1998). The MeSO 2 -PCB concentrations are notably high in the liver of mammals (Larsson and Bergman, 1998, Bergman et al, 1994b) and likewise, human livers have been shown to accumulate MeSO 2 -PCBs (Weistrand and Noren, 1997, Ellerichmann et al, 1998). The majority of these metabolites have the MeSO 2 substituent in the meta -position of their respective biphenyl ring.…”
Section: Pcb Metabolism and Relevant Classes Of Pcb Metabolitesmentioning
confidence: 99%
“…= not detected; LOQ = limit of quantification; a) Sampling year; b) Number of MeSO 2 -PCB congeners in the ΣMeSO 2 -PCB; c) include concentration of the MeSO 2 -hexaCB (unknown); d) The publication year; e) pooled sample/number of subjects in the pool; f) Data has been recalculated for a lipid content of 4%; g) Mean values. References: R1 : (Weistrand et al, 1997); R12 : (Noren et al, 1996); R13 : (Newsome and Davies, 1996); R14 : (Weistrand and Noren, 1997); R15 : (Weistrand and Noren, 1997); R16 : (Guvenius et al, 2002); R17 : (Chu et al, 2003b); R18 : (Chu et al, 2003b). …”
Section: Figurementioning
confidence: 99%
“…The environmental chemical 3-methylsulfonyl-DDE, a metabolite of the lipophilic insecticide DDT, was found to be present in mother's milk, blood and adipose tissue [47,48] and was shown to accumulate in the adrenal cortex. Using human H295R and mouse Y1 adrenocortical cells it was shown that several persistent aryl methylsulfone metabolites of PCBs and DDT, including 3-methylsulfonyl-DDE, competitively inhibit mitochondrial 11␤-hydroxylase, which catalyzes the last step of glucocorticoid synthesis by converting 11-deoxycortisol to cortisol.…”
Section: Disturbed Glucocorticoid Action Due To Altered Function Of Smentioning
confidence: 99%